Linking Zoonosis Emergence to Farmland Invasion by Fluctuating Herbivores: Common Vole Populations and Tularemia Outbreaks in NW Spain - Herrero-Cófreces, Silvia; Mougeot, François; Lambin, Xavier; Luque-Larena, Juan José (Frontiers in Veterinary Science, 2021)
The expansion and intensification of agriculture are driving profound changes in ecosystems worldwide, favoring the (re)emergence of many human infectious diseases. Muroid rodents are a key host group for zoonotic infectious pathogens and frequently invade farming environments, promoting disease transmission and spillover. Understanding the role that fluctuating populations of farm dwelling rodents play in the epidemiology of zoonotic diseases is paramount to improve prevention schemes. Here we review a decade of research on the colonization of farming environments in NW Spain by common voles (Microtus arvalis) and its public health impacts, specifically periodic tularemia outbreaks in humans. The spread of this colonizing rodent was analogous to an invasion process and was putatively triggered by the transformation and irrigation of agricultural habitats that created a novel terrestrial-aquatic interface. This irruptive rodent host is an effective amplifier for the Francisella tularensis bacterium during population outbreaks, and human tularemia episodes are tightly linked in time and space to periodic (cyclic) variations in vole abundance. Beyond the information accumulated to date, several key knowledge gaps about this pathogen-rodent epidemiological link remain unaddressed, namely (i) whether colonizing vole introduced or amplified pre-existing F. tularensis; (ii) which features of the ‘Francisella - Microtus’ relationship are crucial for the epidemiology of tularemia? (iii) how virulent and persistent F. tularensis infection is for voles under natural conditions? and (iv) where does the bacterium persist during inter-epizootics? Future research should focus on more integrated, community-based approaches in order to understand the details and dynamics of disease circulation in ecosystems colonized by highly fluctuating hosts.